O ativismo judicial nos tribunais superiores: uma análise quanto à inconstitucionalidade da súmula 308 do TST. - Monte, Priscila Braz do (2015)
The dissertation has as object of study the judicial activism in the higher courts in particular the emphasis on the Precedent 308 of the Superior Labor Court that would be unconstitutional. Since the Federal Constitution, article 7, XXIX brings standard that regulates the extinctive prescription labor bringing two distinct periods: the five-year prescription (partial) and biennial (total). It turns out that despite the Federal Constitution provides, the workers have two years after the termination of the employment relationship to join the lawsuit claiming credits and can only claim up to five years in default funds during the employment contract. The TST in the docket 308 stipulated that the partial prescription count would be from the filing date and not the termination of the employment relationship which further restricts workers' rights. It aims to analyze based on this doctrinal study if that TST posture driven by the Judicial Activism, with the approach of the Legal Civil Law systems with the common law, would be going beyond the interpretation function of the standard that is the constitutional Judiciary function extrapolating the limits of judicial activism, resulting in the creation of a standard for the limitation period score that therefore violates a basic principle of the Federative Republic of Brazil which is the tripartite division of powers since the created standards is constitutional competence of the Legislature. Moreover, it discusses if such precedent goes against the intent of the constitutional legislator and the constitutional principle of access to justice and the principle of the worker protection, specifically the sub principle of in "dubio pro operario", meaning, in doubt the interpreter should opt for the most favorable interpretation to the worker; this principle is guiding the development and interpretation of the rules in material and labor procedural field. Furthermore, it will examine whether the Precedent 308 is riddled with unconstitutional by transgression of the tripartite division of powers and the fundamental principles governing the employment relationship, considering that the Federal Constitution made clear that the treatment of labor prescription is differentiated from others due worker hyposufficiency because the state's highest law expressly brought the computation is from the termination of the employment relationship and not the injury.